Pengembangan Modul Bimbingan Sosial untuk Meningkatkan Perilaku Prososial Siswa : Development of a Social Guidance Module to Enhance Students' Prosocial Behavior - Darmawansyah; Arman, Muhammad (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
This study aims to investigate the development of a social guidance module to enhance students' prosocial behavior. The research approach used is research and development (R&D). The subjects of this study include expert test subjects, namely academic and practitioner experts, as well as ninth-grade students from State Junior High School (SMP) 5 Tavanjuka Palu for the 2021/2022 academic year. Data was collected using questionnaires and interviews. Data analysis employed both qualitative and quantitative methods. The results of the study indicate that (1) Students exhibited low levels of prosocial behavior, making the social guidance module designed to improve this behavior highly necessary in schools. (2) The developed module is highly engaging and practical for both teachers and students, as it presents materials directly related to students' prosocial behavior issues and includes appealing images that capture students' attention. Additionally, the module is equipped with Student Worksheets (LKS) as an evaluation tool to assess students' understanding and behavior changes after studying it. (3) The implementation of the social guidance module at SMP 5 Tavanjuka Palu has proven to be effective in enhancing students' prosocial behavior.